2017
DOI: 10.3233/bmr-170886
|View full text |Cite
|
Sign up to set email alerts
|

Impact of foot pronation on postural stability: An observational study

Abstract: Foot pronation affects the postural stability at stability level four and not affects stability level eight compared with those in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
10
0
4
Order By: Relevance
“…A pronated foot posture leads not only to mechanical changes, but also to somatosensory alterations [5], and may therefore affect static and dynamic postural stability. As with the results of previous studies [6,15,17,18], the change of postural stability in pronated foot groups was also identified in present study. In particular, our study found the significant differences and correlations in some parameters of dynamic stability under eyes-closed condition.…”
Section: Foot Posture and Postural Stabilitysupporting
confidence: 92%
See 3 more Smart Citations
“…A pronated foot posture leads not only to mechanical changes, but also to somatosensory alterations [5], and may therefore affect static and dynamic postural stability. As with the results of previous studies [6,15,17,18], the change of postural stability in pronated foot groups was also identified in present study. In particular, our study found the significant differences and correlations in some parameters of dynamic stability under eyes-closed condition.…”
Section: Foot Posture and Postural Stabilitysupporting
confidence: 92%
“…The static stability index under the eyes-open and eyes-closed conditions in the current study may therefore not show significant differences regardless of different foot postures. Koura et al [6] also assumed that the level of difficulty in the dynamic balance test may affect their results; in their study, pronated and neutral foot groups were tested at two different BBS stability levels (levels 8 and 4), and a significant difference was found only at the relatively difficult stability level (level 4), which they concluded allows more foot displacement than the easier stability level at which no significant difference was found. Therefore, relatively easy BBS stability levels or task levels might be inappropriate Additionally, according to Tables 3 and 5, no significant results were found in the dynamic APSI under the eyes-closed condition, and there may be a difference in postural stability between the anterior-posterior (AP) direction and the mediallateral (ML) direction.…”
Section: Foot Posture and Postural Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [8][9][10][11] suggested that there were some connections between FPI and KOA. On the one hand, it was reported that some impairments of balance and stability were detected in patients with KOA [12], and FPI was associated with balance and postural stability [13,14], which was very important to reduce the risk of falling in the elderly [15]. On the other hand, it has been proved that there is a biomechanical link between foot posture and adduction moment/altered frontal knee alignment [8], and supinated FPI is related to pain, function in KOA patients [10].…”
Section: Introductionmentioning
confidence: 99%